Novel high-power-factor isolated electronic ballast for multiple tubular fluorescent lamps - Wakabayashi, F. T. [UNESP]; Canesin, C. A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This paper presents a novel isolated electronic ballast for multiple fluorescent lamps, featuring high power-factor, and high efficiency. Two stages compose this new electronic ballast, namely, a new voltage step-down isolated Sepic rectifier, and a classical resonant Half-Bridge inverter. The new isolated Sepic rectifier is obtained from a Zero-Current-Switching (ZCS) Pulse-Width-Modulated (PWM) soft-commutation cell. The average-current control technique is used in this preregulator stage in order to provide low phase displacement and low Total-Harmonic-Distortion (THD) at input current, resulting in high power-factor, and attending properly IEC 61000-3-2 standards. The resonant Half-Bridge inverter performs Zero-Voltage-Switching (ZVS), providing conditions for the obtaining of overall high efficiency. It is developed a design example for the new isolated electronic ballast rated at 200W output power, 220Vrms input voltage, 115Vdc dc link voltage, with rectifier and inverter stages operating at 50kHz. Finally, experimental results are presented in order to verify the developed analysis. The THD at input current is equal to 5.25%, for an input voltage THD equal to 1.63%, and the measured overall efficiency is about 88.25%, at rated load.
Keywords: Ballasts (lamp); Electric current control; Electric inverters; Electric potential; Electric power factor; Electric rectifiers; Harmonic distortion; Pulse width modulation; Switching; Electronic ballast; Total harmonic distortion; Zero current switching; Zero voltage switching; Fluorescent lamps